OPTIMIZED HPLC METHOD FOR SIMULTANEOUS DETERMINATION OF ARTIFICIAL SWEETENERS, PRESERVATIVES, AND CAFFEINE IN CARBONATED SOFT DRINKS - Wardono, Sri; Putra, Effendy De Lux; Sinaga, Siti Morin; Dalimunthe, Aminah; Nasri, Nasri (Talenta Publisher, 2025)
Sweeteners, preservatives, and caffeine in soft drinks can pose health risks if consumed excessively. This study aimed to develop a method for the simultaneous determination of acesulfame, saccharin, cyclamate, aspartame, caffeine, benzoate, and sorbate in carbonated soft drinks. The analysis was conducted using reversed-phase high-performance liquid chromatography (RP-HPLC) with a dual-wavelength PDA detector (Shimadzu LC-20AD), a C18 column (Shimadzu), and a UV-Vis spectrophotometer (Shimadzu). Standard materials included acesulfame-K, saccharin-Na, cyclamate-Na, aspartame, caffeine, benzoate-Na, and sorbic acid. Samples were obtained from a supermarket in Medan, Indonesia. Optimization parameters included detection wavelength, mobile phase pH, column oven temperature, and mobile phase composition. Validation parameters assessed were linearity, limit of detection (LOD), limit of quantification (LOQ), accuracy, precision, and selectivity. The optimized method employed a mobile phase of phosphate buffer (pH 3.8) and methanol (80:20, v/v) at a flow rate of 0.55 mL/min and column oven temperature of 40 °C. Detection was carried out at 200 nm for cyclamate, caffeine, aspartame, and benzoate, and at 220 nm for acesulfame, saccharin, and sorbate. Validation results showed the method met all requirements, with recovery rates ranging from 95.21% to 99.82%, system suitability values of 1.0%–1.9%, and precision values between 1.65% and 2.48%. The method also demonstrated good selectivity. The concentrations of acesulfame, saccharin, cyclamate, caffeine, benzoate, and sorbate in the analyzed samples did not exceed the maximum permissible limits.